2021
DOI: 10.3389/fphar.2021.630434
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Awareness of the Impact of Improperly Disposed Of Medications and Associated Factors: A Cross-Sectional Survey in Indonesian Households

Abstract: Introduction: Disposal of unused medications through environmentally unsafe routes is common in Indonesia. The lack of awareness of the impact of improperly disposed of medications is a significant contributing factor. The objectives of this study were to identify factors associated with lack of awareness of the impact of improperly disposed of unused medications and to assess the associations of awareness with medication disposal practices among the general population in Indonesia.Patients and methods: An obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(33 reference statements)
1
5
0
1
Order By: Relevance
“…In addition, 79.5% agreed to fact that they had never received information about proper medication disposal practices. [19] A similar study by Marwa et al assessed the disposal practice of expired and unused medications at household level among Tanzania population (N=359). The results revealed that 96% kept unused/expired medications in their homes which were supposed to be discarded and disposing of medications practice followed were domestic trashes (75.5%) and pit latrines (15.5%) with 76% aware of the detrimental effect of improper disposal of expired medications to human health and environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 79.5% agreed to fact that they had never received information about proper medication disposal practices. [19] A similar study by Marwa et al assessed the disposal practice of expired and unused medications at household level among Tanzania population (N=359). The results revealed that 96% kept unused/expired medications in their homes which were supposed to be discarded and disposing of medications practice followed were domestic trashes (75.5%) and pit latrines (15.5%) with 76% aware of the detrimental effect of improper disposal of expired medications to human health and environment.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, some people need treatment and medication but cannot afford them. Many people may not know of the best ways to dispose of unused and expired drugs and there is a need to make the public aware of this and to assist in the proper gathering of unused pharmaceutical products [ 5 , 18 , 19 ]. Bridging all these issues and addressing them through the deployment of the website and device was the focus of our research.…”
Section: Discussionmentioning
confidence: 99%
“…Di Australia, program take-back obat yang disebut kampanye Return Unwanted Medicines berhasil mengumpulkan 700 ton obat-obatan yang tidak diinginkan pada tahun 2015-2016, membantu mencegah mereka dibuang secara tidak tepat dan menyebabkan kerusakan lingkungan [3]. Memperbaiki praktik pembuangan obat yang tidak terpakai saat ini di Indonesia akan membutuhkan metode terorganisir untuk mengumpulkan obat yang tidak digunakan dari masyarakat dan membuangnya dengan benar melalui kebijakan praktis seperti program pengobatan take-back berbasis farmasi [17]. Selain itu, program Gema Cermat (Gerakan Masyarakat Cerdas Menggunakan Obat) dan Dagusibu (Dapatkan, Gunakan, Simpan dan Buang) melibatkan apoteker sebagai agen perubahan untuk meningkatkan penggunaan obat-obatan secara rasional di masyarakat [18,19].…”
Section: Hasil Dan Diskusiunclassified